Isolation and Selection of Antagonistic Bacteria against Cercospora arachidicola Causing Brown Spot on Peanut - Khang Le Thanh; Thao Tran Yen (Bogor Agricultural University, Indonesia, 2023)
This study was conducted with the aim to isolation bacterial strains capable of antagonism to Cercospora arachidicola (Passalora arachidicola) causing brown spot in peanut. From 3 soil samples collected in the rhizosphere of peanut grown in Tay Ninh province, Vietnam, 10 bacterial strains were found having antagonistic action with Cercospora arachidicola. After 5 days of testing, the antagonistic efficiency of all isolates ranged from 33.33±1.28 to 60.183±0.927%. Studying the antagonistic mechanism showed that 5/10 isolates produced siderophore, 5/10 isolates were capable of decomposing chitin, 7/10 isolates capable of decomposing cellulase and 8/10 isolates proteolytic. Basing on the results of 16S rRNA gene sequence combined with morphological and biochemical characteristics, TN-TB 4, TN-TB 6 and TN-TB 12 were identified as Bacillus, representing the genera Bacillus amyloliquefaciens, Bacillus pasterurii, and Bacillus velezensis, respectively. These strains of antagonistic bacteria have the potential to produce probiotics.